2023
DOI: 10.1002/vetr.3174
|View full text |Cite
|
Sign up to set email alerts
|

Assessing primary care veterinarians’ use of and confidence in performing point‐of‐care ultrasound

Abstract: BackgroundPoint‐of‐care ultrasound (POCUS) is gaining popularity in the veterinary field, but there is little information on operator confidence.MethodsA survey was distributed to primary care veterinarians (PCVs) via social media between May and July 2020. Details of participants' training in and use of POCUS were recorded. Participants' confidence in using thoracic and abdominal POCUS was also assessed using a five‐point Likert scale.ResultsTwo hundred and one PCVs used POCUS, of which 32% reported using a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…These findings may suggest that imaging of the heart is more challenging or that training in the specific area is less accessible. 19,22 Other ultrasound assessments that were performed less commonly and with low confidence included the detection of adrenal and pancreatic abnormalities, detection of lymph node and musculoskeletal abnormalities, detection of pneumothorax and measurement of the optic nerve sheath diameter. This suggests that the assessment of these organs or abnormalities likely requires more advanced training and that these abnormalities may be less well-researched in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings may suggest that imaging of the heart is more challenging or that training in the specific area is less accessible. 19,22 Other ultrasound assessments that were performed less commonly and with low confidence included the detection of adrenal and pancreatic abnormalities, detection of lymph node and musculoskeletal abnormalities, detection of pneumothorax and measurement of the optic nerve sheath diameter. This suggests that the assessment of these organs or abnormalities likely requires more advanced training and that these abnormalities may be less well-researched in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…40 We found that most small animal practitioners with access to an ultrasound unit have less than 25 h of training and are not uncommonly self-educated, similar to the study of primary care veterinarians in the United Kingdom. 22 The optimal number of training hours or supervised exams for a veterinarian to have a basic level of proficiency for limited ultrasound assessments has not been determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation